2017
DOI: 10.1186/s12877-017-0420-9
|View full text |Cite
|
Sign up to set email alerts
|

The temporal impact of aging on the burden of herpes zoster

Abstract: BackgroundThe risk of Herpes Zoster (HZ) increases with age and various studies have also demonstrated an increasing HZ incidence globally. Simultaneously, the global trend of an aging population has placed a greater burden on the healthcare system. This study aims to estimate the potential burden of HZ over time accounting for the increasing trends of both HZ incidence and global aging.MethodsA recent systematic review on HZ incidence identified studies that evaluated the temporal effects of HZ incidence. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 25 publications
1
58
0
1
Order By: Relevance
“…Previously, for this same study population we found that IRs for HZ were higher in females compared with males and increased with greater age, and were highest in patients with IC conditions (and in particular those undergoing HSCT, subjects with HM and those with SLE), and somewhat lower in subjects with chronic medical conditions . Those findings are consistent with those from other epidemiological studies which report an increasing incidence of HZ with older age, and also a higher incidence in patients with malignancy, and other IC conditions such as SLE . In the further data we present here, we show that the influence of age and sex is also apparent in patients with different IC and chronic medical conditions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previously, for this same study population we found that IRs for HZ were higher in females compared with males and increased with greater age, and were highest in patients with IC conditions (and in particular those undergoing HSCT, subjects with HM and those with SLE), and somewhat lower in subjects with chronic medical conditions . Those findings are consistent with those from other epidemiological studies which report an increasing incidence of HZ with older age, and also a higher incidence in patients with malignancy, and other IC conditions such as SLE . In the further data we present here, we show that the influence of age and sex is also apparent in patients with different IC and chronic medical conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The lifetime risk for developing HZ is estimated at 30% . Declining VZV‐specific cell‐mediated immunity, which predisposes an individual to VZV reactivation and clinical HZ, occurs as a result of age‐related “immunosenescence”, which may explain the greater risk and higher incidence of HZ in individuals aged 50 years or more . Incidence and risk is greater in women, in individuals with immunocompromised (IC) medical conditions (e.g., patients with hematological or solid tumors or those receiving immunosuppressive therapies) and also in individuals with certain chronic medical conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 HZ is a painful and costly condition estimated to result in approximately $1.3 billion in medical care costs and $1.7 billion in indirect costs in the US annually; 3 this burden is projected to rise substantially over the coming years due to aging populations. 4 In 2008, the Advisory Committee on Immunization Practices (ACIP) recommended that adults aged 60+ years old be vaccinated against HZ. 5 A live attenuated zoster vaccine, Zostavax (Zoster Vaccine Live [ZVL]) (currently licensed for use in healthy adults aged 50+ years old), is a one-dose vaccine that utilizes the same Oka strain as in varicella vaccines but at a higher potency.…”
Section: Introductionmentioning
confidence: 99%
“…Pasien geriatrik seperti pada kasus ini memang berisiko lebih tinggi terkena herpes zoster karena beberapa faktor seperti peningkatan penggunaan vaksin varicella, populasi manula yang meningkat, kondisi kronis penyerta, dan meningkatnya penggunaan terapi imunosupresif. 8,9 Terapi antivirus bertujuan untuk mempercepat penyembuhan lesi, mengurangi pembentukan lesi baru, mengurangi pelepasan virus, dan mengurangi nyeri. Terapi antivirus paling bermanfaat pada pasien immunocompromised, berusia > 50 tahun, dengan nyeri atau ruam yang berat.…”
Section: Diskusiunclassified